Product Differentiation and Competitive Selection - Serguei Kaniovski (Austrian Institute of Economic Research (WIFO), 2005)
By studying the effect of different patterns of demand in an evolutionary selection model this paper shows how product differentiation reduces competitive selection pressure and thus increases the chances for the coexistence of firms. With the example of a duopoly it shows that: (1) a monopoly is the likely outcome of competition in homogeneous products, (2) although product differentiation does not preclude a monopoly it greatly improves the chances for the stable coexistence of firms in the long run, and (3) the more differentiated the products, the more stable the duopoly.
Keywords: B52; L11; 330; product differentiation; selection; market niche; Produktdifferenzierung; Nischenstrategie; Wettbewerb; Duopol; Evolutionäre Spieltheorie